PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KOMPETENSI GURU TERHADAP PRESTASI KERJA GURU - Ilmi Noor Rahmad (Prima Magistra: Jurnal Ilmiah Kependidikan, 2021)
The work performance of a teacher today is an inseparable part of our world of education. Currently, being a quality teacher has become an absolute requirement. There are many factors that influence the creation of teacher performance in the school organizations. Some of them are related is principal leadership and teacher performance role. The research aim of this research is to note how the relationship between principal leadership and teacher competence partially and can be influenced teacher performance at SMP Widya Nusantara, Bekasi, West Java. This research method is through a quantitative approach with a questionnaire obtained from 30 respondents. The research result shows that there is a positive and significant relationship between principal leadership and teacher performance. This matter can be observed from t value (5,291) > t table (1,703), then Ho unaccepted and H1 accepted. There is also positive and significant relationship between teacher competence with teacher performance. This matter can be observed from t value (8,307) > t table (1,703), then Ho unaccepted and H2 accepted. From this calculation significant coefficient multiple correlation test obtainable F value = 17,482 > F table at the error level (a) 1% = 7,677. Therefore, it can be concluded that the correlation coefficient between principal leadership and teacher competence is in accordance with teacher performance is significant. It means Ho unaccepted and H3 accepted, in the sense is principal leadership (X1) and teacher competence (X2) is in accordance positively related and significant to performance teacher variable (Y) at SMP Widya Nusantara. Whereas, Correlation Coefficient Value (r) as big as 0,751 means is 75,1% of principle leadership and teacher competence are related to teacher performance at SMP Widya Nusantara, whereas the rest as big as 24,9% related to other factors that unobserved by the researcher.